Physical behaviours during pregnancy may alter the association of maternal insulin sensitivity with neonatal adiposity: a prospective pre-birth cohort of mother-child pairs - Piraveena Satkunanathan; Catherine Allard; Myriam Doyon; Patrice Perron; Luigi Bouchard; Marie-France Hivert; Tricia M. Peters (BMC Pregnancy and Childbirth)
Abstract Background Lower maternal insulin sensitivity during pregnancy is associated with greater fetal adiposity. Physical activity can improve insulin sensitivity, but it is not known if physical behaviours influence the known association of maternal insulin sensitivity with offspring adiposity. This study aimed to investigate the moderating impact of physical behaviours on this association. Methods Pregnant women (n = 812) from the Gen3G cohort were recruited during the first trimester of pregnancy and followed until delivery. At the first (V1) and second trimester (V2) hospital visits, Gen3G staff measured anthropometry, and participants reported sleep duration as well as leisure physical activity and sedentary behaviour via lifestyle questionnaires. We used plasma glucose and insulin values from the 75 g oral glucose tolerance test at V2 to calculate insulin sensitivity using the Matsuda index. We recorded birthweight from electronic medical records. Among a subset of neonates (n = 265), trained research staff measured skinfold thickness using a calibrated skinfold caliper following standardized protocols to estimate neonatal adiposity. Linear regression analyses assessed the association of insulin sensitivity with birthweight z-score and sum of neonatal skinfold thickness, adjusting for maternal age, race/ethnicity, gravidity, smoking, with and without adjustment for maternal body mass index at V1. We evaluated moderation by physical activity, sedentary behaviour, or nighttime sleep duration using interaction terms and stratified analyses for the association of maternal insulin sensitivity with offspring birthweight and with offspring adiposity. Results Lower Matsuda index was associated with higher birthweight z-score (ß±SE= -0.180 ± 0.056, p = 0.001) and with higher sum of skinfold thickness (neonatal adiposity) (ß±SE=-0.877 ± 0.383, p = 0.02) in fully adjusted models. The association between Matsuda index and sum of skinfold thickness was weaker in women with higher levels of physical activity at V2 ([high ≥ 1.26 kcal/kg/day] ß±SE=-0.15 ± 0.65) compared to women with lower levels [low < 1.26 kcal/kg/day] ß±SE=-1.36 ± 0.51, P-interaction = 0.01). We also observed potential interactions of sleep and sedentary behaviour at V2 with Matsuda index for the association with birthweight z-score. We did not observe effect modification by levels of physical behaviours assessed at V1. Conclusion The association between lower insulin sensitivity and higher neonatal adiposity was attenuated in women with higher physical activity levels in the second trimester, independent of maternal body mass index.